Integrated Infrastructure Management Using Web-GIS Application: Integrated Infrastructure Management Using Web-GIS Application - Abdul Wahid, Muhammad Aqiff; Abdul Maulud, Khairul Nizam; Rahman, Muhammad Amartur; Saiful Bahri, Mohd Aizat (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The aim of this research is to build a web application using Geographic Information System (GIS) Technology and at the same time can assist the university in managing infrastructure asset. Infrastructure assets information which is stored using conventional methods such as in paper form; paper maps; and drawings are not reliable anymore. However, this information can be used by converting them into a geospatial data format. Furthermore, a geodatabase is created to store all the information. Spatial data and attribute data are connected to each other in the geodatabase. ArcGIS Desktop is an application to create, manage, edit, manipulate, visualize and publish geospatial data. The publish service will be used in ArcGIS Online and act as a medium to customize a webmap application. The webmap application is capable to provide and visualize the spatial and non-spatial information of each infrastructure asset. In addition, assets information can easily be shared among the university management and with the advantage of GIS mapping, the information can be understood by everyone. The research investigates the infrastructure asset management using ArcGIS Online and how it can improve the conventional method of asset management.